Multilevel analysis of factors associated with assistance during delivery in rural Nigeria: implications for reducing rural-urban inequity in skilled care at delivery - Bola Lukman Solanke; Semiu Adebayo Rahman (BMC, 2018)
Abstract Background Studies have observed rural-urban inequity in the use of skilled delivery in Nigeria. A number of studies have explicitly examined associated factors of assistance during delivery in rural areas. However, the studies so far conducted in rural Nigeria have investigated mainly individual-level characteristics with near exclusion of community-level characteristics. Also, most of the studies that have investigated community-level influence on use of maternal healthcare services in Nigeria did not isolate rural areas for specific research attention. The objective of this study was to investigate the individual-level and community-level characteristics associated with assistance during delivery in rural Nigeria. Methods The study analysed women data of 2013 Nigeria Demographic and Health Survey. A weighted sample size of 12,665 rural women was analysed. The outcome variable was assistance during delivery, dichotomised into 'skilled assistance' and 'unskilled assistance'. The explanatory variables are selected individual-level characteristics (maternal education, parity, age at first birth, religion, healthcare decision, employment status, access to mass media, and means of transportation); and selected community-level characteristics (community literacy level, community childcare burden, proportion of women employed outside agriculture, proportion of women who perceived distance to facility as a big problem, community poverty level, and geographical region). The mixed-effects logistic regression was applied. Results During the most recent deliveries, 23.0% of rural women utilised skilled assistance compared with 77.0% who utilised unskilled assistance. Maternal education, parity, religion, healthcare decision, access to mass media, and means of transportation were the individual-level characteristics that revealed significant effects on the likelihood of utilising skilled assistance during delivery, while community literacy level, community poverty level, community perception of distance to health facility, and geographic region were the community-level characteristics that revealed significant effects on the odds of using skilled assistance during delivery. Results of Intra-Class Correlation (ICC) supported significant community-level effects on the likelihood of using skilled assistance during delivery. Conclusions Assistance during delivery is influenced by individual-level and community-level characteristics. Health policies and programmes seeking to reduce rural-urban inequity in skilled delivery should endeavour to identify and address important factors at both the individual and community levels of the social environment.